Pharmacokinetic study on the co-administration of abemaciclib and astragaloside IV in rats. (31st December 2022) - Sun, Sen; Liu, Lu; Song, Hongming; Li, Hong
Abstract: Context: The co-administration of abemaciclib and astragaloside IV might occur in the treatment of breast cancer. Objective: This study evaluates the interaction between abemaciclib and astragaloside IV in rats and describes the potential mechanism. Materials and methods: Male Sprague Dawley rats were randomly divided into four groups: single dose of abemaciclib (control), abemaciclib + 50 mg/kg/d astragaloside IV, abemaciclib + 100 mg/kg/d astragaloside IV, and abemaciclib + 150 mg/kg/d astragaloside IV. Abemaciclib and astragaloside IV were orally administrated, and astragaloside IV was pre-administrated for 7 d in the co-administrated groups. The pharmacokinetics and transport of abemaciclib were assessed in the absence or presence of astragaloside IV. In mechanism, the activity of CYP3A4 was estimated in human liver microsomes in the presence of astragaloside IV. Results: Astragaloside IV significantly increased the Cmax (from 991.5 ± 116.99 up to 2308.5 ± 55.29 μg/L) and AUC (from 24.49 ± 2.86 up to 66.14 ± 1.17 μg/mL × h) and prolonged the t1/2 (from 19.85 ± 4.65 up to 66.17 ± 28.73 h) of abemaciclib, and the effect was enhanced with the increasing astragaloside IV concentration. Astragaloside IV also suppressed the transport of abemaciclib with the efflux ratio decreasing to 1.35. Astragaloside IV suppressed the activity of CYP3A4 with an IC50 value of 21.78 μM. Discussion and conclusions: The co-administration of abemaciclib and astragaloside IV induced the increasing systemic exposure of abemaciclib through the inhibition of CYP3A4. Further clinical validations could be carried out according to the study design of the present investigation.